1991
DOI: 10.1002/hep.1840140109
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C viral RNA in serum of patients with chronic non-A, non-B hepatitis: Detection by the polymerase chain reaction using multiple primer sets

Abstract: The recently introduced antibody test for hepatitis C virus infection has already proved to be valuable in many situations such as screening blood donors and diagnosing chronically infected patients, but this antibody assay has certain limitations. Hepatitis C virus itself is usually present in clinical specimens at very low titers; therefore a useful assay for the virus must have very high sensitivity. We have developed a simple, highly sensitive assay for hepatitis C virus RNA based on the polymerase chain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(35 citation statements)
references
References 13 publications
1
34
0
Order By: Relevance
“…This method can detect a single point mutation and is widely used to screen mutations in various oncogenes (Cottrell et at., 1992). In addition, the nested PCR used in the present study to generate the ssDNA is known to have the same level of specificity as Southern blot hybridization for the detection of a target gene (Cristiano et al, 1991).…”
Section: Discussionmentioning
confidence: 94%
“…This method can detect a single point mutation and is widely used to screen mutations in various oncogenes (Cottrell et at., 1992). In addition, the nested PCR used in the present study to generate the ssDNA is known to have the same level of specificity as Southern blot hybridization for the detection of a target gene (Cristiano et al, 1991).…”
Section: Discussionmentioning
confidence: 94%
“…Unfortunately, in the absence of an efficient in vitro replication system or convenient animal model, the causal relationship between CTL and variant viral peptide sequence in HCV infection cannot be tested directly (34)(35)(36). Furthermore, our stimulation method does not allow us to distinguish between immunodominant versus subdominant epitopes nor could we study the CTL response and virus sequence from the onset of their infection.…”
Section: Discussionmentioning
confidence: 99%
“…The viral cDNA was amplified by PCR with appropriate precautions to prevent PCR contamination as described by Kwok and Higuchi (27), and the PCR products were analyzed on a 1.5% agarose gel and visualized by ethidium bromide staining. The primer sets and PCR conditions to amplify the ten epitopes are described as follows: PCR products containing the HCV fragment were sequenced with the corresponding internal HCV primers, Sequenase 2.0 (Amersham Corp., Arlington Heights, IL), 35 S dATP (Amersham Corp.) using dideoxynucleotide chain-termination method according to the manufacturer's instructions, analyzed on a 6% denaturing acrylamide gel, and autoradiographed. Ambiguous or variant (i.e., non-HCV-1) sequences were confirmed by sequencing of both sense and antisense strands, and/or by sequencing of second independently amplified PCR product.…”
Section: Methodsmentioning
confidence: 99%
“…Although the time required for the development of HCV-specific antibodies after acute infection is reduced, these tests remain unsatisfactory for the diagnosis of acute infection. HCV RNA PCR, performed in individual research laboratories, has rapidly become the diagnostic standard for HCV infection (19)(20)(21)(24)(25)(26)(27)(28)(29). Most investigators prefer primers from the 5' UTR since HCV nt analyses have indicated that the 5' UTR has a very high homology (2 97%) among different HCV strains (8,13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, multiple weeks are required for development of anti-HCV after HCV infection (18), which precludes the use of anti-HCV for the diagnosis of acute infection. The second technique detects HCV RNA through a reverse transcription and polymerase chain reaction (HCV RNA PCR) (19)(20)(21). Although HCV RNA PCR is a sensitive technique, extensive application is limited by cost, labor intensity, risk of false-positive resultsthrough contamination (22,23), and disparate results among laboratories using different primers (21,24 (25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%